Quantification of carbohydrates in human serum using gas chromatography–mass spectrometry with the stable isotope-labeled internal standard method. (27th May 2022) - Zhang, Ming-Jia; Zhao, Jin-Hui; Tang, Ying-Shu; Meng, Fan-Yu; Gao, Si-Qi; Han, Su; Hou, Shao-Ying; Liu, Li-Yan
Abstract : Comparison of two derivatization approaches (silylation and acylation) for carbohydrate separation based on optimizing reaction conditions by artificial neural networks. Abstract : Carbohydrates are crucial in determining the metabolic alterations that occur in various diseases. The separation and detection of carbohydrates in biological samples are particularly difficult because of their structural similarities. A comparative analysis of silylation and acylation derivatization protocols for carbohydrates in serum was performed using gas chromatography-triple quadrupole mass spectrometry and the stable isotope-labeled internal standard method. A comprehensive investigation was performed with regard to the pretreatment of serum, conditions of the derivatization reaction, robustness toward matrix effects, validation of the method, and quantitation using a set of reference compounds that comprised nine monosaccharides, lactose, galacturonic acid, and glucuronic acid. Both approaches offered strong linearity and sensitivity, as well as acceptable accuracy and precision. The limits of quantitation (LOQ) of the silylation protocol varied from 0.0010 to 1.2500 μg mL −1, while the correlation coefficients of regression curves ranged from 0.9871 to 0.9996. The satisfactory correlation coefficients in acylation protocol (0.9869–0.9991) were obtained, while the LOQ ranged from 0.0003 to 2.8432 μg mL −1 . The separation conditions revealed that 12 carbohydrates were detected in silylation, but lactose and galacturonic acid peaks were not obtained in the acylation protocol. However, the acylation approaches were superior to the silylation approaches due to the high stability of derivatives, minor relative standard deviations (0.05–8.67), and low sensitivity toward matrix effects. Finally, we applied two protocols to the serum samples from the patients with gastric carcinoma. This protocol was, in particular, of great importance in the quantitative analysis of complex carbohydrate profiles in human serum, providing novel insights into the change in the carbohydrate metabolism for the disease.